2022
DOI: 10.3389/fbioe.2022.891407
|View full text |Cite
|
Sign up to set email alerts
|

Cell Inertia: Predicting Cell Distributions in Lung Vasculature to Optimize Re-endothelialization

Abstract: We created a transient computational fluid dynamics model featuring a particle deposition probability function that incorporates inertia to quantify the transport and deposition of cells in mouse lung vasculature for the re-endothelialization of the acellular organ. Our novel inertial algorithm demonstrated a 73% reduction in cell seeding efficiency error compared to two established particle deposition algorithms when validated with experiments based on common clinical practices. We enhanced the uniformity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous studies have utilized decellularized mouse lungs for cell repopulation; however, the culture conditions were either static using decellularized lung slices 10 or not physiologically relevant where mouse lungs were incubated in a rotating syringe 11 . Recent literature has reported that a mouse-scale dynamic culture platform could enhance the repopulation of epithelial cells in decellularized mouse lung scaffolds, which led us to extend the platform to vascular engineering with proper vascular access 12,13 . Herein, we expand on this platform to optimize and evaluate the endothelialization of acellular mouse lung scaffolds.…”
mentioning
confidence: 99%
“…Previous studies have utilized decellularized mouse lungs for cell repopulation; however, the culture conditions were either static using decellularized lung slices 10 or not physiologically relevant where mouse lungs were incubated in a rotating syringe 11 . Recent literature has reported that a mouse-scale dynamic culture platform could enhance the repopulation of epithelial cells in decellularized mouse lung scaffolds, which led us to extend the platform to vascular engineering with proper vascular access 12,13 . Herein, we expand on this platform to optimize and evaluate the endothelialization of acellular mouse lung scaffolds.…”
mentioning
confidence: 99%